Seasonal variations of bio‐optical properties and their interrelationships observed by Bio‐Argo floats in the subpolar North Atlantic. Issue 10 (31st October 2014) - Xing, Xiaogang; Claustre, Hervé; Uitz, Julia; Mignot, Alexandre; Poteau, Antoine; Wang, Haili
Abstract Based on in situ data sets collected using two Bio‐Argo floats deployed in the subpolar North Atlantic from June 2008 to May 2010, the present study focuses on the seasonal variability of three bio‐optical properties, i.e., chlorophyll‐a concentration ([Chla]), particle backscattering coefficient at 532 nm (bbp(532)), and particle beam attenuation coefficient at 660 nm (cp(660)). In addition, the interrelationships among these properties are examined. Our results show that: (1) [Chla], bbp(532) and cp(660) are largely well coupled with each other in the upper layer, all being minimum in mid‐winter (January) and maximum in summer; (2) the backscattering coefficient presents an abrupt increase in late summer in the Icelandic Basin, likely due to a large contribution of coccolithophores following the diatom spring bloom; (3) the intercorrelations between the three bio‐optical properties are basically consistent with previous studies; (4) seasonal variation in the of [Chla] to cp(660) ratio exhibits a clear light‐dependence, most likely due to the phytoplankton photoacclimation.